1994
DOI: 10.1002/bjs.1800810206
|View full text |Cite
|
Sign up to set email alerts
|

Venous and non-venous leg ulcers: Clinical history and appearance in a population study

Abstract: In a defined Swedish population of 270,800, all patients with current chronic leg ulcers (827) were identified and a random sample of 382 studied in detail. Ulcers of primarily venous cause comprised 54 per cent of the total, giving a point prevalence of 0.16 per cent (95 per cent confidence interval 0.15-0.18 per cent). Half of all patients experienced their first ulcer episode before the age of 65 years, a greater proportion (61 per cent, P < 0.0001) in the subgroup with venous ulcers. The median duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
149
0
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(168 citation statements)
references
References 10 publications
10
149
0
8
Order By: Relevance
“…Sixty to 80% of leg ulcers have a venous component. [1][2][3][4][5][6][7] The Lothian and Forth Valley Study examined 600 patients with leg ulceration and found that 76% of ulcerated legs had evidence of venous disease and 22% had evidence of arterial disease. Ten to 20% of cases had both arterial and venous insufficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty to 80% of leg ulcers have a venous component. [1][2][3][4][5][6][7] The Lothian and Forth Valley Study examined 600 patients with leg ulceration and found that 76% of ulcerated legs had evidence of venous disease and 22% had evidence of arterial disease. Ten to 20% of cases had both arterial and venous insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…8 Chronic venous leg ulceration has an estimated prevalence of between 0.1% and 0.3% in the United Kingdom. [1][2][3][4][5][6]9 Prevalence increases with age. 8 Approximately 1% of the population will suffer from leg ulceration at some point in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among people aged 65 years and older, the annual prevalence of VLUs is 1.7%. 3 Of all types of chronic ulcers, VLUs have the worst long-term healing prognosis and are more likely to be recurrent.…”
Section: Introductionmentioning
confidence: 99%
“…3 Of all types of chronic ulcers, VLUs have the worst long-term healing prognosis and are more likely to be recurrent. 2,4 In fact, half of the patients diagnosed with VLUs have an ulcer duration greater than 1 year and recurrence has been estimated at > 75% of those affected. 1,2 With such long ulcer duration and high recurrence rate, patients presenting for wound care can be at any point along this continuum, and often have an extensive medical history with several comorbidities and complex medication regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation